Testbeam results of the Picosecond Avalanche Detector proof-of-concept prototype. (1st October 2022) - Iacobucci, G.; Zambito, S.; Milanesio, M.; Moretti, T.; Saidi, J.; Paolozzi, L.; Munker, M.; Cardella, R.; Martinelli, F.; Picardi, A.; Rücker, H.; Trusch, A.; et al.
Abstract: The proof-of-concept prototype of the Picosecond Avalanche Detector, a multi-PN junction monolithic silicon detector with continuous gain layer deep in the sensor depleted region, was tested with a beam of 180 GeV pions at the CERN SPS. The prototype features low noise and fast SiGe BiCMOS frontend electronics and hexagonal pixels with 100 μm pitch. At a sensor bias voltage of 125 V, the detector provides full efficiency and average time resolution of 30, 25 and 17 ps in the overall pixel area for a power consumption of 0.4, 0.9 and 2.7 W/cm 2, respectively. In this first prototype the time resolution depends significantly on the distance from the center of the pixel, varying at the highest power consumption measured between 13 ps at the center of the pixel and 25 ps in the inter-pixel region.